2020
DOI: 10.1002/admi.202000571
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Electrolyte Solution Dual‐Mode Electrospinning Process for In Situ Fabrication of Electrospun Bilayer Membrane

Abstract: vivo extracellular matrix (ECM). [2] Various advantages of the electrospun nanofiber membranes, including broad material selection, a high surface-area-to-volume ratio, controllability of physical properties (e.g., diameter and orientation of the nanofibers and porosity and thickness of the membrane), and capability in fabrication of complex nanostructures (e.g., coreshell and Janus nanofibers), [3] have made remarkable advancements in the development of in vitro tissue models and in vivo tissue regeneration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Our results showed that the micro-ridge patterns on the IPC-CE construct favorably promoted both the elongation and orientation of cells along the micro-ridges by geometrical confinement, which stably maintained their structure during the cell culture period, whereas the conventional constructs lost their topographical effect following rehydration. Although in the present study, we considered only a simple in vitro cell culture, the proposed IPC-CE construct may have various biomedical applications, such as the development of an in vitro model for mimicking the hierarchical topography of native tissues and a scaffold/wound dressing for promoting in vivo tissue regeneration [ 36 , 37 ]. Moreover, given that the attachment, alignment, and elongation of cells resulted from their sensing and response to the surrounding cell environment [ 38 , 39 ], a more profound understanding of in vivo cell-surface topography interactions may be accomplished from in-depth investigations of cell behaviors on micro-patterned constructs with in vivo-like collagen nanofibrillar architectures.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the micro-ridge patterns on the IPC-CE construct favorably promoted both the elongation and orientation of cells along the micro-ridges by geometrical confinement, which stably maintained their structure during the cell culture period, whereas the conventional constructs lost their topographical effect following rehydration. Although in the present study, we considered only a simple in vitro cell culture, the proposed IPC-CE construct may have various biomedical applications, such as the development of an in vitro model for mimicking the hierarchical topography of native tissues and a scaffold/wound dressing for promoting in vivo tissue regeneration [ 36 , 37 ]. Moreover, given that the attachment, alignment, and elongation of cells resulted from their sensing and response to the surrounding cell environment [ 38 , 39 ], a more profound understanding of in vivo cell-surface topography interactions may be accomplished from in-depth investigations of cell behaviors on micro-patterned constructs with in vivo-like collagen nanofibrillar architectures.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a number of membranes were wetted with a physiological solution (sodium chloride (NaCl) 0.9%) and subsequently compared to the dry membranes. Three tensile test scenarios were selected for which the strain rate was set at 10 mm/min: 2628 a standard metal clamp, a paper frame and the new clamp were tested and compared so as to observe their effectiveness and their measurement reproducibility ( n = 12). As the jaws were designed for the more rapid clamping of samples, the time required for the placing of samples in the paper frame, including the time required to prepare the paper frame, were compared with the time required for the placing of samples in the printed jaws.…”
Section: Methodsmentioning
confidence: 99%
“…Each end of the specimen was gripped in a clamp and its tensile properties was tested at a constant tensile speed of 10 mm min − 1 , using a customized testing machine comprising a linear actuator and a load cell with a resolution of 0.01 gf. [18] The resultant force-distance curve was converted to a stress-strain curve for evaluating the elastic modulus, ultimate tensile strength, and resilience.…”
Section: Mechanical Propertiesmentioning
confidence: 99%